PEMODELAN ALIRAN DAYA PADA SISTEM ENERGI MOBIL LISTRIK - Kaloko, Bambang Sri (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2010)
The issue of the depletion of oil reserves in the world, and the problem of air pollution produced by motor vehicles, motivate many researchers to seek alternative energy sources to propel the vehicle. One promising way is to replace combustion motor with an electric motor, which is known as an electric car. First stage of this research is to model the flow of power in the electric car energy system to obtain its characteristics. Power flow efficiency in electric cars is very important because this type of car is highly dependent on the limited electrical energy supplied by a battery. Therefore it should be managed properly. This study is to look into the power flow calculation so that the amount of electrical energy is in accordance with the needs of electric cars. A model using Simulink software is to get the best power flow response to the electric car energy system.